(untitled) (REMUNOM, 2026)
Laboratory animals maintained under specific pathogen-free (SPF) conditions are essential to ensure the reliability and reproducibility of biomedical research. Individually ventilated cage (IVC) rack systems contribute to preserving the sanitary status of animal colonies; however, contamination events may still occur. Conventional monitoring strategies, such as random animal screening or soiled bedding sentinel (SBS) programs, exhibit limited sensitivity, particularly for pathogens transmitted via aerosols or direct contact. In this context, exhaust air particle sampling combined with polymerase chain reaction (PCR)-based molecular detection has emerged as a promising alternative. This study evaluated the detection of pathogens in aerosolized particles collected from ventilated racks at Laboratory Animal Breeding Centers in Minas Gerais, Brazil. Lactobacillus sp. was used as a positive control, and Rodentibacter pneumotropicus served as a model respiratory pathogen. A total of 74 samples were collected from three sampling sites: exhaust filters (n = 16), resident animal cages/top filters (n = 46), and mini-isolators containing soiled bedding (n = 12). Molecular analysis demonstrated higher and more consistent DNA recovery from exhaust filters, whereas mini-isolators yielded low detectable DNA concentrations. The absence of R. pneumotropicus detection, together with consistent recovery of the positive control, supports the feasibility and reliability of the proposed protocol for environmental health surveillance. This methodology shows potential for further optimization and may contribute to reducing or replacing sentinel animals, in accordance with the principles of the 3Rs (Replacement, Reduction, and Refinement) in animal experimentation.